Fatigue: Is it all neurochemistry? - Meeusen, R.; Roelands, B. (European Journal of Sport Science, 2018)
Fatigue during exercise can be approached from different angles. Peripheral fatigue is usually described as an impairment located in the muscle and characterized by a metabolic end point, while central fatigue is defined as a failure of the central nervous system to adequately drive the muscle. The aim of the present narrative review paper is to look at the mechanisms involved in the occurrence of fatigue during prolonged exercise, predominantly from a brain neurochemical point of view. From studies in rodents it is clear that exercise increases the release of several neurotransmitters in different brain regions, and that the onset of fatigue can be manipulated when dopaminergic influx in the preoptic and anterior hypothalamus is increased, interfering with thermoregulation. This is however not as straightforward in humans, in which most studies manipulating brain neurotransmission failed to change the onset of fatigue in normal ambient temperatures. When the ambient temperature was increased, dopaminergic and combined dopaminergic and noradrenergic reuptake inhibition appeared to override a safety switch, allowing subjects to push harder and become much warmer, without changing their perception. In general, we can conclude that brain neurochemistry is clearly involved in the complex regulation of fatigue, but many other mediators also play a role.